Pendekatan Maqāṣid al-syarī‘ah Kontemporer dalam Perilaku Ekonomi - Landy T. Abdurrahman (Indonesia, 2019)
The Contemporary Maqāṣid asy-Syarī‘ah Approach in Economic Behavior The maqāṣid asy-Syarī‘ah (objectives of syariah) have become a growing discussion in the contemporary Islamic world. Maqāṣid asy-Syarī‘ah is now developed into an approach, not just as a concepts. The maqāṣid asy-Syarī‘ah approach should be applicable to various problems and also should be used to measure the extent to which the objectives of Shari'a are realized in human behavior also in human’s economic behavior. The maqāṣid asy-Syarī‘ah approach developed by Jasser Auda has put the maqāṣid asy-Syarī‘ah as a philosophical foundation for the existence of Islamic law. Maqāṣid asy-Syarī‘ah approach is no longer the normative measure of a Islamic law (fiqh) product, but rather the application and implications of the establishment of a product of Islamic law (fiqh).